The combination of PIVKA‐II and AFP improves the detection accuracy for HCC in HBV caucasian cirrhotics on long‐term oral therapy. (23rd May 2020) - Loglio, Alessandro; Iavarone, Massimo; Facchetti, Floriana; Di Paolo, Dhanai; Perbellini, Riccardo; Lunghi, Giovanna; Ceriotti, Ferruccio; Galli, Claudio; Sandri, Maria T.; Viganò, Mauro; Sangiovanni, Angelo; Colombo, Massimo; et al.
Abstract: Background & Aims: Protein induced by vitamin K absence or antagonist‐II (PIVKA‐II) has been suggested as a serum biomarker for hepatocellular carcinoma (HCC) in Asian hepatitis B virus (HBV)‐treated subjects but no studies tested it in Caucasian cirrhotics long‐term nucleos(t)ide analogues (NUCs)‐treated. We assessed the detection accuracy of PIVKA‐II alone or in combination with alpha‐foetoprotein (AFP) in patients under surveillance. Methods: This cross‐sectional, single centre case‐control study was conducted in 212 NUC‐treated cirrhotics: 64 HCC and 148 HCC‐free controls for 84 (60‐107) months. PIVKA‐II was determined by a CMIA immunoassay (Abbott; limit of quantification: 8.2 mAU/mL). Results: Protein induced by vitamin K absence or agonist II (PIVKA‐II) and AFP levels were significantly higher in HCC patients [Barcelona Clinic Liver Cancer staging system stage 0/A in 91%, diameter 20 (6‐50) mm] compared to controls: 109 (17‐12 157) vs 31 (13‐82) mAU/mL and 5 (1‐1163) vs 2 (1‐7) ng/mL ( P  < .001 for both markers), with a cut‐off of 48 mAU/mL and 4.2 ng/mL by AUROC analysis. The PIVKA‐II 82 mAU/mL and AFP 7 ng/mL cut‐offs showed 100% specificity, with the former more sensitive (54% vs 42%), accurate (86% vs 83%), with higher negative predictive value (80% vs 76%) compared to AFP for HCC detection. PIVKA‐II more frequently than AFP levels exceeded the cut‐off 6‐18 months before HCC diagnosis. Combining PIVKA‐II with AFP increased sensitivity, accuracy and negative predictive values to 67%, 90% and 85%, preserving 100% specificity. PIVKA‐II was associated with lesions >20 mm or neoplastic thrombosis. Conclusions: Combination of PIVKA‐II and AFP increases the detection rate for HCC in NUC‐treated HBV Caucasian cirrhotics, a potential new approach for surveillance.